Gonadotropin-Releasing Hormone (GnRH) Agonist Implants for Male Dog Fertility Suppression: A Review of Mode of Action, Efficacy, Safety, and Uses - Driancourt, Marc Antoine; Briggs, Joyce R. (Frontiers in Veterinary Science, 2020)
At present, only surgical sterilization is available for veterinarians and pet owners seeking suppression of fertility in male dogs, in most countries. An alternative contraceptive alternative approach is GnRH releasing implants that desensitize the pituitary to the stimulatory effects of GnRH and thereby block testicular function (testosterone and sperm production). Two GnRH agonists (deslorelin and azagly-nafarelin) have been researched in controlled release formulations for this purpose. A deslorelin-releasing biodegradable implant, marketed under the name Suprelorin®, has been available in Australia and New Zealand since 2007, the European Union (EU) since 2008, and received regulatory approval in China and Mexico in late 2019. Two versions of the implant are available, one labeled for a minimum of 6 months of fertility suppression in male dogs, and the other for a minimum of 12 months in male dogs. Another GnRH agonist (azagly-nafarelin) was also included in a solid implant (Gonazon®). Research results showed it delivered six-months to one year of suppressed fertility; however, it not commercialized. This review paper summarizes research on the mechanism of action for these technologies and compiles and interprets the research on efficacy and safety. New findings on usage of the deslorelin releasing implant in countries where veterinarians and pet owners have this option is shared. Research on off-label use of the product in male dogs is also reviewed. This review aims to aid in the evaluation of the deslorelin releasing implant as an adjunct or alternative for surgical sterilization of male dogs.